Clinico-pathological study of intradural extramedullary spinal tumors - Venugopal, Gudla; Rao, A. Lakshman; Jyothi, Sangam M. (International Journal of Research in Medical Sciences, 2017)
Background: The intradural extramedullary tumours of the spine are one of the commonest tumours of the spine. Early diagnosis and surgical removal helps in best outcome. The objective of the study was to analyze the clinical presentation, imageology, resectability, to know the incidence of different types of tumours in intradural extramedullary compartment and to study the surgical outcome. Methods: This was a prospective study of 32 cases of intradural extramedullary tumours. The clinical presentation, imageology, resectability, histopathology, surgical outcome were studied. The patients were investigated with plain spinal radiography and MRI. All cases were treated surgically by posterior or posterolateral approaches. Outcome and complications were evaluated. They were followed up regularly and the results were analyzed. Ambulatory status was classified on admission by using Nurick-grading scheme. Results: The incidence of intradural extramedullary spinal tumours was 57.14%. Most of the tumours presented in the third decade (37.5%). Mean age of Presentation for meningioma was 36 years and for nerve sheath tumours was 39.5 years. The nerve sheath tumours contributed 35% followed by meningioma 28%. Nerve sheath tumours were found to be most commonly located in thoracic region (56%). Total excision of tumour was achieved in 87.7% cases. Conclusions: Nerve Sheath tumours and Meningiomas were the most common in intradural extramedullary spinal lesions and complete excision was possible in almost all cases. Prognosis was usually good, in spite of poor neurological status at the time of presentation.